Efektivitas Penerapan Artificial Intelligence pada Fitur Chat Shopee terhadap Peningkatan Penjualan, Kualitas Pelayanan, dan Efisiensi Ekonomi Digital - Lindawati; Kiki Dwi Wijayanti (Prodi Ilmu Komunikasi Fakultas Komunikasi & Desain Kreatif, 2026)
This study aims to analyze the effectiveness of implementing Artificial Intelligence (AI) in the automated chat feature of the Shopee e-commerce platform and its impact on sales growth, service quality, and digital economic efficiency. The integration of AI into customer service has transformed interaction patterns between sellers and buyers by enabling faster, more consistent, and error-minimized responses. This research employs a mixed-methods approach by combining quantitative and qualitative data. Quantitative data were collected through a survey of 120 Shopee users who had interacted with the automated chat feature, while qualitative data were obtained through in-depth interviews with 12 active sellers utilizing the AI Chat Response feature. The results indicate that the implementation of AI significantly reduced message response time from an average of 4.8 minutes to 27 seconds. This improvement in response speed directly contributed to an increase in message-to-transaction conversion rates of up to 38% and customer satisfaction levels reaching 92%. Furthermore, sellers who adopted the AI Chat Response feature experienced an average sales increase of 18.6% over the three-month research period. Analysis based on the Unified Theory of Acceptance and Use of Technology (UTAUT2) and the E-Service Quality framework demonstrates that AI significantly enhances perceived usefulness, perceived ease of use, and overall digital service quality. These findings confirm that AI adoption not only improves sellers’ operational efficiency but also plays a strategic role in fostering digital economic growth in Indonesia.